2020
DOI: 10.1038/s41598-020-66927-5
|View full text |Cite
|
Sign up to set email alerts
|

FACS-Based Functional Protein Screening via Microfluidic Co-encapsulation of Yeast Secretor and Mammalian Reporter Cells

Abstract: in this study, we present a straightforward approach for functional cell-based screening by coencapsulation of secretor yeast cells and reporter mammalian cells in millions of individual agarosecontaining microdroplets. our system is compatible with ultra-high-throughput selection utilizing standard fluorescence-activated cell sorters (FACS) without need of extensive adaptation and optimization. In a model study we co-encapsulated murine interleukin 3 (mIL-3)-secreting S. cerevisiae cells with murine Ba/F3 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 54 publications
(39 reference statements)
0
43
0
Order By: Relevance
“…Researchers have also reported the use of DFC for the screening of co-cultures of mammalian cells and yeast cells. Individual yeast secretors (e.g., S. cerevisiae 103 and Pichia pastoris 104 ) and mammalian reporter cells were co-encapsulated and cultivated in agarose microdroplets, which is followed by FACS to select clones secreting bioactive recombinant proteins. These studies demonstrated the feasibility of DFC for screening and isolation of protein variants produced by microbes, which would enable and accelerate the discovery of new functional biologics, such as cytokines, antibodies, and soluble receptors.…”
Section: Cell-to-cell Interactionmentioning
confidence: 99%
“…Researchers have also reported the use of DFC for the screening of co-cultures of mammalian cells and yeast cells. Individual yeast secretors (e.g., S. cerevisiae 103 and Pichia pastoris 104 ) and mammalian reporter cells were co-encapsulated and cultivated in agarose microdroplets, which is followed by FACS to select clones secreting bioactive recombinant proteins. These studies demonstrated the feasibility of DFC for screening and isolation of protein variants produced by microbes, which would enable and accelerate the discovery of new functional biologics, such as cytokines, antibodies, and soluble receptors.…”
Section: Cell-to-cell Interactionmentioning
confidence: 99%
“…In this approach, CHO cells, transfection to stably expressing the Trastuzumab IgG, were sorted based on magnetic markers of target proteins (Figure 11A). Another strategy used Gel microdroplet (GMD) -fluorescence activated cell sorting (Yanakieva et al, 2020). P pastoris expressing full-length monoclonal antibodies and mammalian target cells were co-encapsulated in GMDs, then IgG antibodies bound to the epidermal growth factor receptor (EGFR) target cells were detected by fluorescently labeled antibodies for FACS screening (Fang, Chu, Ackerman, & Griswold, 2017) (Figure 11B).…”
Section: Antibody Expression Technologymentioning
confidence: 99%
“…[12][13][14] Antibodies secreted from single cells are interrogated after compartmentalization in droplets, 15 nanostructures such as nanopens, 16 or microcapillaries. [17][18][19] Most antibody secreting cells are plasma cells obtained from rodent immunization, 20 but also differentiated memory B cells, plasma blasts from human peripheral blood, 21,22 or secretion libraries 23 are applied. Antibodies screened by microfluidics retain their native chain pairing, which can be assessed by next-generation sequencing (NGS), 24 used for direct antibody subcloning or subsequent library generation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Compatible with the high throughput of microfluidic setups, mostly fluorescence-based methods are applied for real-time adjustable mining of large diversities. Methodologies range from selection for binding on the recombinant target or cells 26 to internalization or functional screening using reporter gene target cells, 23,27,28 as exemplified by the recent work from Gérard et al 20 While broad diversities of neutralizing antibodies against infectious diseases such as HIV, Ebola, or COVID-19 have been identified from convalescent individuals, 22,29,30 microfluidics can also yield tools 16 as well as therapeutic antibodies targeting cancer or immunological diseases. 31,32 Several companies offer custom and customizable microfluidic chips for commercial and academic antibody screening campaigns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation